Downhole manipulation systems for abrasive jet cutting on oil wells. - Aldridge, Antony (Cranfield University, 1997)
This project investigates the possibility of using abrasive water jets for cutting operations inside oil wells and presents the associated procedures and tools required. Through-tubing window cutting was identified as an application of particular interest to the oil industry. This involves cutting a hole in the well casing, below the production tubing, so that a new well can be directionally drilled through it and into the producing formation. The study showed that through-tubing window cutting is a feasible application for abrasive water jets. The main findings are: • a 2.5 m by 0.1 m window can be cut in 10 mm thick casing in approximately 12 hours. This assumes that the window is 3000 m from the surface and that a surface pressure of 595 bar is used. • a manipulator has been designed in detail, based on a pressure balanced cylinder, which can move the nozzle smoothly and accurately over the complete surface area of the window. The maximum outer diameter is 53 mm and it would be deployed on VA” coiled tubing. Test rigs have confirmed the operation of critical components of the design. • several aspects of the design still need to be tested. A prototype manipulator should be built to demonstrate that it can repeatedly cut the same size of window and operate continuously for over 20 hours. • the pressure balanced design principle is applicable to any abrasive water jet cutting manipulator in which the nozzle is perpendicular to the direction of the well. Two examples are perforation of short sections of casing and cutting around the circumference of the production tubing for removal. • a specially designed cutting fluid with appropriate polymer additives must be used to give excellent solids carrying properties and low pressure loss. Their effect on cutting performance and hole cleaning efficiency needs to be tested.
Keywords: Water jets; abrasive; cutting; oil wells; through-tubing window